Use of occupational health services in a Cyprus oncology center - Provan, Helen; Raftopoulos, Vasilios; Soteriades, Elpidoforos Soterakis (My University, 2009)
Use of occupational health services in the hospital environment is an important parameter for annual health care planning. The objective of this study was to evaluate the clinic utilization at a Cyprus oncology center. All visits to the occupational health clinic during an 18-month period were reviewed and analyzed. During the study period, the center had, on average, 161 employees and offered 67 occupational health clinic sessions. Employees had 338 clinic visits, of which 294 were primary and 44 were follow-up visits, with 5 employees, on average, visiting the clinic at each session. Nurses most frequently visited the center (33.4%), followed by the administrative staff (28.6%) and the employees of the Medical Physics and Radiology Department (22.4%), corresponding to the largest groups of employees. The most frequently cited reason for the visits was administrative purposes (23.6%), including updating health records, followed by pre-placement examinations (14.7%) and vaccinations (10.3%). Administrative and clinical reasons were given for occupational health clinic use at the oncology center across all categories of employees.
Keywords: Nursing; Hospitals; Occupational health services